2017
DOI: 10.1002/jcla.22105
|View full text |Cite
|
Sign up to set email alerts
|

Relation of serum and vitreous nesfatin-1 concentrations with diabetic retinopathy

Abstract: Serum and vitreous nesfatin-1 concentrations were negatively correlated with DR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 22 publications
(30 reference statements)
3
9
0
1
Order By: Relevance
“…Li et al first investigated the fasting plasma levels of nesfatin-1 in type 2 diabetes patients and found that fasting nesfatin-1 levels were significantly lower in the type 2 diabetes group compared with the levels in healthy subjects [ 12 ]. Several subsequent studies also reached the same conclusion [ 10 , 11 , 13 , 14 ]. However, Zhang et al reached the opposite conclusion [ 9 ].…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…Li et al first investigated the fasting plasma levels of nesfatin-1 in type 2 diabetes patients and found that fasting nesfatin-1 levels were significantly lower in the type 2 diabetes group compared with the levels in healthy subjects [ 12 ]. Several subsequent studies also reached the same conclusion [ 10 , 11 , 13 , 14 ]. However, Zhang et al reached the opposite conclusion [ 9 ].…”
Section: Discussionsupporting
confidence: 61%
“…These results showed no evidence of heterogeneity and explained part of the heterogeneity problem of the full analysis. As four studies from the antidiabetic treatment subgroup were located in China [ 11 – 14 ], we next performed pooled analysis, and the result was similar to that for the antidiabetic treatment subgroup [ Figure 2(c) , MD = −0.27; 95% CI (−0.34 and −0.20), P < 0.00001, I 2 = 0%].…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…Similarly, mRNA and protein expression is significantly reduced in the islets of Goto-Kakizaki (GK) rats, a model of type 2 diabetes (8). It has also been shown that fasting plasma nesfatin-1 levels are significantly reduced in T2DM (15)(16)(17), whereas plasma nesfatin-1 in type 1 diabetic patients was unchanged compared with healthy individuals (17). Accordingly, the concentrations of nesfatin-1 in the serum and milk of gestational diabetic lactating women is lower than that of control participants (18).…”
Section: Introductionmentioning
confidence: 99%